Effects of the reduction of dietary heat increment on the performance, carcass yield, and diet digestibility of broilers submitted to heat stress - Laganá,C (2007)
This experiment aimed at verifying the effect of different diets and thermal environments on the performance, carcass yield, and diet digestibility of 21 to 42-day-old broilers. A total number of 288 21-day-old male Ross broilers were distributed in a 2 x 2 + 2 factorial arrangement, with six replicates, including the following factors: two environments (TNE - thermoneutral: 21-25ºC and 73% RH; CHS - cyclic heat stress: 25-32ºC and 65%RH), and two diets (control: 2.4% soybean oil and 19.5% protein; summer: 4.0% soybean oil and 18.5% protein). In TNE, two additional treatments were included with feed restriction of birds fed both the control and summer diets (pair-feeding), thereby maintaining the same feed intake level for both types of diet. Diet did not influence performance, dry matter and protein digestibilities, or carcass and part yields. TNE birds had better performance (p<0.001) as compared to CHS birds, but FCR was not different. CHS birds had lower breast yield (p<0.0001), and higher thigh yield (p<0.02) than TNE birds. In the pair-feeding treatments, environment did not influence performance, but dry matter digestibility was significantly lower in CHS (p<0.03), whereas protein digestibility was not affected. The difference in feed intake was the main responsible factor for the variation in the performance of heat-stressed birds.